DIFFERENTIATION OF CONDITIONS FOR MOBILE GAMES FOR CHILDREN WITH DIFFERENT DEGREES OF MOTOR DISORDERS - Naumova, E.V.; Maltseva, I.S.; Vinogradova, A.V.; Berestova, D.E. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to differentiate the conditions for conducting outdoor games in the process of adaptive physical education of children with cerebral palsy with varying degrees of motor impairment. Methods and structure of the study. The pedagogical experiment was conducted at the Tchaikovsky State Academy of Physical Culture and Sports from September to December 2021. Extracurricular classes on adaptive physical education for children with cerebral palsy were organized. The main content of the classes was corrective outdoor games. The subjects were 16 children with cerebral palsy aged 3 to 12 years of varying severity. Before the start of classes, the primary diagnosis of children was carried out according to the following scales: determination of global motor function disorders (GMFCS); dysfunction of the hands and manual skills MACS; impaired communication function (CFCS); definition of mobility of the child (FMS). According to the diagnostic results, all children were divided into 3 groups, depending on the severity of motor disorders. Results of the study and their discussion. Based on the primary diagnosis, the conditions for conducting active game were selected, which were adapted depending on the severity of motor disorders in children. The following components were subjected to differentiation: initial position, type of movement in the game, dosage, and the role of the child in the game. During the experiment period, statistically significant changes occurred in children of the 3rd group in terms of: fine motor skills, coordination of movements, muscle spasticity.